Early language ability and the trajectory of internalizing problems across childhood: the mediating role of maternal parenting practices - Ting, Sharon (2024)
Early language problems and poor parenting practices are associated with more internalizing problems across childhood. However, scant research has directly examined the mediating role of parenting practices. Utilizing a sample of 309 mother-child dyads (49.8% females) from Singapore’s largest birth cohort study, we investigated whether maternal parenting practices mediate the association between children’s language abilities and growth trajectory of internalizing problems.